Stand-Alone Cervical Cage for Cervical Radiculopathy: A Retrospective Study - Martiana, I Ketut; Tumbelaka, Reyner Valiant ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2020)
Background: Cervical radiculopathy is a clinical condition characterized by unilateral arm pain, numbness and tingling in a dermatomal distribution in the hand, and weakness in specific muscle groups. This condition can be treated with nonsurgical or surgical methods. This study aims to evaluate the outcome of the stand-alone cervical cage surgical method for cervical radiculopathy at our hospital institution from 2013 to 2017.Methods: This is a retrospective observational study on every patient who underwent a stand-alone cervical cage procedure for cervical radiculopathy at our hospital institution from 2013 to 2017. The study was conducted from December 2017 until April 2018. We evaluated the clinical outcome with the Neck Disability Index (NDI). The data were collected from medical records, and postoperative follow-up was done by house visits, phone calls, and outpatient visits.Results: Five male and one female subject with a mean age of 58 years (range, 45–65 years) underwent the procedure; one patient passed away three years postoperatively due to events unrelated to the operation; one patient could no longer be reached. Four patients had an increasing NDI score postoperatively. There were no postoperative complications.Conclusion: Stand-alone cervical cage appears to be a safe and effective treatment, providing a favorable clinical outcome for cervical radiculopathy at our hospital institution from 2013 to 2017.